Redefining the health system: A proposed updated framework of a systems approach to health - Alaeddini, Farshid; Tavolinejad, Hamed; Esmailzadeh, Hamid (Frontiers in Public Health, 2022)
Defining the health system, as a multidimensional and complex structure, is challenging, and the existing definitions often fail to incorporate the various levels and functions involved in a single system definition. An ideal framework should be easy to evaluate, allow for comparison, and be divisible into smaller sub-systems for easier interpretation. This paper concisely explores a novel framework to perceive health systems. As in any system, it is important to accurately define the health system's input, process, and output, as the cornerstone of evaluating any system is to assess outputs with regard to inputs besides analyzing outcomes, impact, objectives, and values. Since the raison d'être of the health system is to improve health in society, it is proposed that the input can be considered as the population subject to the system's process, and the output as the population with improved health status. This paper also proposes defining support systems, whose input and output are needs and parts of the process in the main system, respectively. Example support systems include the health evidence production or education and development of human resources systems. Instead of considering all functions as part of the main system, this concept allows implementation and assessment of policies in various levels of health systems to be simplified, as each support system can be separately evaluated with clear functions.